Silybin and dehydrosilybin inhibit cytochrome P450 1A1 catalytic activity: a study in human keratinocytes and human hepatoma cells - Dvorák, Z; Vrzal, R; Ulrichová, J (Cell biology and toxicology, 2006)
The flavonolignan silybin and its derivative dehydrosilybin have been proposed as candidate UV-protective agents in skin care products. This study addressed the effect of silybin and dehydrosilybin on the activity of cytochrome P450 isoform CYP1A1 in human keratinocytes (HaCaT) and human hepatoma cells (HepG2). CYP1A1 catalytic activity was assessed as O-deethylation of 7-ethoxyresorufin using fluorescence detection. Silybin and dehydrosylibin inhibited basal and dioxin-inducible CYP1A1 catalytic activity in both cell lines used. The inhibitory effect of tested compounds was more pronounced in HaCaT cells than in HepG2 cells, and dehydrosilybin was a much stronger inhibitor than silybin. Analyses on CYP1A1 human recombinant protein yielded IC(50) values of 22.9 +/- 4.7 micromol/L and 0.43 +/- 0.04 micromol/L for silybin and dehydrosilybin, respectively. Since CYP1A enzymes are some of the most prominent actors in the process of chemically induced carcinogenesis, the inhibitory activity of the flavonolignans tested against CYP1A1 favors their use as cytoprotective agents in terms of skin and hepatic metabolism. In addition, the capability of dehydrosilybin to inhibit CYP1A1 in submicromolar concentrations makes this compound a potential biological probe in CYP1A1 analyses.
Keywords: Silymarin; viabilita buněk; Cell Line; silibinin; Cell Line, Tumor; Dioxins; Cytochrome P-450 CYP1A1; molekulární struktura; Molecular Structure; Carcinoma, Hepatocellular; vztah mezi dávkou a účinkem léčiva; Cell Survival; dioxiny; cytochrom P-450 CYP1A1; Keratinocytes; silymarin; Silybin; Time Factors; keratinocyty; lidé; enzymová indukce; Humans; časové faktory; hepatocelulární karcinom; buněčné linie; Enzyme Induction; nádorové buněčné linie; Liver Neoplasms; Dose-Response Relationship, Drug; nádory jater